Pengaruh Komitmen Diri dan Motivasi Diri Terhadap Kinerja Guru Agama Buddha Tingkat Sekolah dasar Se-Jabodetabek - Bagus Sasongko KW (Institut Nalanda, 2023)
KW, Bagus Sasongko (2022) The Influence of self-Commitment and Selft-Motivation on the Performen of Buddhist Teacher at elementary School in Jabodetabek. Thesis of the Postgraduate Buddhist Education Masters Study Program at Nalanda Buddhist College Jakarta Advisor I Dr.Muljadi, S.Kom., MM., M.BA, Advisor II Dr.Sutrisno., S.IP., M.Si This study was to examine the effect of self-commitment on techer performance, to examine the effect of self- motivation on teacher performance, and to examine the effect of self-commitment and self-motovation on teacher performance at elementary school level Buddhist teschers throughout Greater Jakarta. The total population in this study were 130 respondents. The sample used is a saturated sample. This type of research uses quantitative analysis. Furthermore, to test the hypothesis used computer tools SPSS Release 18.00 program at a 95% confidence level (α=0.05). The results showed that the 95% confidence level was a positive effect of self-commitment on the performance of the Buddgist teachers at the elementary school level (ry1=0.993;t=96.653;0.05=1.978;0.01=2.553), there was a positive effect. Self-motivation on the performance of Buddhist teacher at the elementary school level (ry2=0.990;tcount=81.272;α 0.05=1978;α 0.01=2.355), and there is a positive effect of self-commitment and self- motivation together on teacher performance elementary school Buddhist teacher (ry1.2=0.994;tcount=11.141;α 0.05=1.656;0.01=2.355). Thus, the higher the self-commitment and self-motivation of a teacher, the higher the tacher’s performance.